ANALISIS PENERAPAN WHISTLEBLOWING SYSTEM DAN DAMPAKNYA PADA PENCEGAHAN KECURANGAN KARYAWAN - Yasir, Muhammad; Sulhani, Sulhani (Jurnal Riset Akuntansi, 2025)
This study aims to evaluate the impact of the whistleblowing system on preventing employee kecurangan in Sharia commercial banks in Indonesia. It examines whether the system serves not only as a kecurangan detection tool but also as an effective preventive mechanism in Sharia banking operations. Using a quantitative approach, this research applies panel data regression analysis to assess the relationship between whistleblowing system implementation and kecurangan levels. The data is sourced from the annual reports of Sharia banks registered with the Financial Services Authority (OJK) from 2021 to 2023. Samples were selected through purposive sampling based on whistleblowing system implementation. The findings indicate that while the system effectively detects kecurangan, it does not significantly contribute to kecurangan prevention. Further improvements are needed to enhance its preventive function.